PERBEDAAN PENGGUNAAN PENDEKATAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER DAN THINK PAIR SHARE TERHADAP KEMAMPUAN MENULIS TEKS CERPEN SISWA KELAS VII SMP NEGERI 12 PADANG - Fitri, Rahayu (BAHASTRA, 2017)
This research were aims to describe the things as follows. First, the ability to write a short story text students of class VII SMP Negeri 12 Padang taught by using cooperative approach Numbered Head Together type. Second, the ability to write short story text students of class VII SMP Negeri 12 Padang taught by using cooperative approach Think Pair Share type. Third, the difference in ability to write short story text students of class VII SMP Negeri 12 Padang taught by cooperative approach Numbered Head Together and Think Pair Share type. This research was quantitative with descriptive method of quasi experimental research design. Sampling was done by using simple random sampling technique. In this research, class VII.3 was assigned as experiment class I which amounted to 32 students and VII.5 as experiment class II which amounted to 30 students. Data collected by using performance test writing short story text. The results of this study are as follows. First, the ability to write a short story text students of class VII SMP Negeri 12 Padang taught by using cooperative approach Numbered Head Together type was 89,58. Second, the ability to write short story text students of class VII SMP Negeri 12 Padang taught by using cooperative approach Think Pair Share type was 81,48. Third, there was a significant difference in ability to write short story text of students in class VII SMP Negeri 12 Padang taught by cooperative approach Numbered Head Together and Think Pair Share type.